Documenting the documentary : close readings of documentary film and video - Grant, Barry Keith; Sloniowski, Jeannette; Nichols, Bill; Rothman, William; Feldman, Seth; Hershfield, Joanne; Sobchack, Vivian; Guynn, William; Tomasulo, Frank P.; Keil, Charlie; Waugh, Thomas; Leach, Jim; et al. (Detroit : Wayne State University Press, 2013)
Anthology of essays on the artistic and persuasive aspects of documentary film from a range of critical viewpoints.
The filmmaker as hunter : Robert Flaherty's Nanook of the north / William Rothman -- "Peace between man and machine" : Dziga Vertov's Man with a movie camera / Seth Feldman -- Paradise regained : Sergei Eisenstein's Que viva México! as ethnography / Joanne Hershfield -- Synthetic vision : the dialectical imperative of Luis Buñuel's Las hurdes / Vivian Sobchack -- The art of national projection : Basil Wright's Song of Ceylon / William Guynn -- The mass psychology of fascist cinema : Leni Riefenstahl's Triumph of the will / Frank P. Tomasulo -- American documentary finds its voice : persuasion and expression in The plow that broke the plains and the city / Charlie Keil -- "Men cannot act before the camera in the presence of death" : Joris Ivens's The Spanish earth / Thomas Waugh -- The poetics of propaganda : Humphrey Jennings and Listen to Britain / Jim Leach -- "It was an atrocious film" : Georges Franju's Blood of the beasts / Jeannette Sloniowski -- The "dialogic imagination" of Jean Rouch : covert conversations in Les maîtres fous / Diane Scheinman -- Documenting the ineffable : terror and memory in Alain Resnais's Night and fog / Sandy Flitterman-Lewis -- Making the past present : Peter Watkins's Culloden / John R. Cook -- "Don't you ever just watch?" : American cinema verité and Dont look back / Jeanne Hall -- "Ethnography in the first person" : Frederick Wiseman's Titicut follies / Barry Keith Grant -- The two avant-gardes : Solanas and Getino's The hour of the furnaces / Robert Stam -- Seeing with experimental eyes : Stan Brakhage's The act of seeing with one's own eyes / Bart Testa -- "A bastard union of several forms" : style and narrative in An American family / Jeffrey K. Ruoff -- The documentary of displaced persona : Michael Rubbo's Daisy, the story of a facelift / Joan Nicks -- Gender, power, and a cucumber : satirizing masculinity in This is spinal tap / Carl Plantinga -- Documentary film and the discourse of hysterical/historical narrative : Ross McElwee's Sherman's march / Lucy Fischer -- Subjectivity lost and found : Bill Viola's I do not know what it is I am like / Catherine Russell -- Mirrors without memories : truth, history, and The thin blue line / Linda Williams -- Documentaphobia and mixed modes : Michael Moore's Roger & me / Matthew Bernstein -- Silence and its opposite : expressions of race in Tongues untied / Sheila Petty -- Containing fire : performance in Paris is burning / Caryl Flinn -- Contested territory : Camille Billops and James Hatch's Finding Christa / Julia Lesage -- Spike Lee's 4 little girls : the politics of the documentary interview / Paula J. Massood -- The gleaners and "us" : the radical modesty of Agnès Varda's Les glaneurs et la glaneuse / Virginia Bonner -- "You must never listen to this" : lessons on sound, cinema, and mortality from Werner Herzog's Grizzly man / David T. Johnson -- Cultural learnings of Borat for make benefit glorious study of documentary / Leshu Torchin.
Bibliografija: str. 543-548.- Kazalo
Keywords: Documentary films -- History and criticism; dokumentarni film